Dentate gyrus granule cell activation following extracellular electrical stimulation: a multi-scale computational model to guide hippocampal neurostimulation strategies - Farzad, Shayan; Wei, Tianyuan; Bouteiller, Jean-Marie C.; Lazzi, Gianluca (Frontiers in Computational Neuroscience, 2025)
IntroductionThe effectiveness of neural interfacing devices depends on the anatomical and physiological properties of the target region. Multielectrode arrays, used for neural recording and stimulation, are influenced by electrode placement and stimulation parameters, which critically impact tissue response. This study presents a multiscale computational model that predicts responses of neurons in the hippocampus—a key brain structure primarily involved in memory formation, especially the conversion of short-term memories into long-term storage—to extracellular electrical stimulation, providing insights into the effects of electrode positioning and stimulation strategies on neuronal response.MethodsWe modeled the rat hippocampus with highly detailed axonal projections, integrating the Admittance Method to model propagation of the electric field in the tissue with the NEURON simulation platform. The resulting model simulates electric fields generated by virtual electrodes in the perforant path of entorhinal cortical (EC) axons projecting to the dentate gyrus (DG) and predicts DG granule cell activation via synaptic inputs.ResultsWe determined stimulation amplitude thresholds required for granule cell activation at different electrode placements along the perforant path. Membrane potential changes during synaptic activation were validated against experimental recordings. Additionally, we assessed the effects of bipolar electrode placements and stimulation amplitudes on direct and indirect activation.ConclusionStimulation amplitudes above 750 μA consistently activate DG granule cells. Lower stimulation amplitudes are required for axonal activation and downstream synaptic transmission when electrodes are placed in the molecular layer, infra-pyramidal region, and DG crest.SignificanceThe study and underlying methodology provide useful insights to guide the stimulation protocol required to activate DG granule cells following the stimulation of EC axons; the complete realistic 3D model presented constitutes an invaluable tool to strengthen our understanding of hippocampal response to electrical stimulation and guide the development and placement of prospective stimulation devices and strategies.